2020
DOI: 10.3390/ijerph17197290
|View full text |Cite
|
Sign up to set email alerts
|

World Trade Center Health Program: First Decade of Research

Abstract: The terrorist attacks on 11 September 2001 placed nearly a half million people at increased risk of adverse health. Health effects research began shortly after and continues today, now mostly as a coordinated effort under the federally mandated World Trade Center (WTC) Health Program (WTCHP). Established in 2011, the WTCHP provides medical monitoring and treatment of covered health conditions for responders and survivors and maintains a research program aimed to improve the care and well-being of the affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 168 publications
(264 reference statements)
0
33
0
Order By: Relevance
“…The general responders were more racially and ethnically diverse compared to FDNY responders who were mostly non-Hispanic, white, and male. 3 Of the total responders in the program, 3,439 are deceased; the primary causes of death were aerodigestive illness (34%), cancer (30%), and mental ill health (15%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general responders were more racially and ethnically diverse compared to FDNY responders who were mostly non-Hispanic, white, and male. 3 Of the total responders in the program, 3,439 are deceased; the primary causes of death were aerodigestive illness (34%), cancer (30%), and mental ill health (15%).…”
Section: Resultsmentioning
confidence: 99%
“…On January 2, 2011, the James Zadroga 9/11 Health and Compensation Act of 2010 (Zadroga Act) was signed into law and the World Trade Center (WTC) Health Program (WTCHP) was created to monitor and treat responders and survivors with 9/11-related adverse health conditions. 3 Eligibility details for inclusion in the program are available elsewhere. [4][5][6] Health data from responders are collected by the WTCHP and summarized to inform a range of research outputs, including the program statistics reported by the Centers for Disease Control and Prevention (CDC; Atlanta, Georgia USA).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2011, these studies have been mostly funded by the WTC Health Program. Detailed information on WTC Health Program research is available online (https://wwwn.cdc.gov/ResearchGateway) and elsewhere 9 . Briefly, WTC Health Program‐funded research examines a wide array of physical and mental health conditions to reduce diagnostic and treatment uncertainty among Program members, uncover new information on listed health conditions, and identify and characterize emerging health conditions that may be related to 9/11 exposures.…”
Section: How Petitions Are Reviewedmentioning
confidence: 99%
“…The WTCHP also maintains a research program aimed to inform the clinical care of program members. In their review, Santiago-Colón et al [ 1 ] describe the research findings of the first decade of the Program and discuss future research directions. The focus of research has been characterizing the burden and etiology of WTC-related health conditions.…”
Section: Wtchp First Decade Of Researchmentioning
confidence: 99%